On energy harvesting from a vibro-impact oscillator with dielectric membranes. (July 2018) - Lai, Z.H.; Thomson, G.; Yurchenko, D.; Val, D.V.; Rodgers, E.
Highlights: Novel vibro-impact energy harvesting system with dielectric elastomers is studied. Complex dynamics of the device is studied under an external harmonic excitation. Output depends on inclination angle, restitution coefficient and initial conditions. Presented results can be used to optimize the device design and inclination angle. Abstract: A vibro-impact mechanical system comprising of a ball moving freely between two dielectric membranes located at a certain distance from each other is studied. The system generates electricity when the ball moving due ambient vibrations impacts one of the membranes. The energy harvesting principle of the proposed system is explained and then used to formulate a numerical model for estimating the system output voltage. The dynamic behavior and output performance of the system are thoroughly studied under a harmonic excitation, as well as different initial conditions and various values of the restitution coefficient of the membranes. The delivered research results are useful for selecting the system parameters to achieve its optimal output performance in a realistic vibrational environment. Potential application of the proposed system for energy harvesting from car engine vibrations is presented.